Royall Tyler and His Evaluation of the Treaty of Trianon - Peterecz, Zoltán (AMERICANA E-journal of American Studies in Hungary, 2020)
The Trianon Treaty after World War I can only be compared to the tragedy of Mohács in 1526. In both cases the Hungarian nation suffered in the wake of a lost war such losses that defined its history and the nation’s mental situation for a long time. The collective trauma that Hungarians had to endure in the two decades after the Trianon Treaty was signed was perhaps the sharpest in all of the Hungarian history. Foreigners often expressed their opinion regarding this peace treaty in the interwar years. Royall Tyler, an American citizen and an officer of the League of Nations was no exception. Tyler, who spent more than a decade in Hungary in the 1920s and 1930s, and knew Hungary and Hungarians exceptionally well, sometimes formulated thoughts on the question of the changed borders. His opinions are interesting because he was an American, and most Hungarians hoped for a possible revision with the help of the United States. Also, foreigners were detached form the Hungarian collective mind and could formulate much more realistic views concerning the Central European situation and possibilities. The article is focusing on Tyler and his vision concerning immediate post-Trianon Hungary and the larger question of possible changes in the peace treaty.